Comparison of clinical presentation and incidence of cardiopulmonary complications between male and female Thai patients with early systemic sclerosis: inception cohort study - Suparaporn Wangkaew (2019)
© 2019, International League of Associations for Rheumatology (ILAR). Objectives: To determine the prevalence of clinical manifestations and incidence rate of cardiopulmonary complications in a comparison between men and women with early SSc. Methods: An inception cohort of early-SSc patients at the Rheumatology Clinic, Maharaj Nakorn Chiang Mai Hospital, between January 2010 and June 2016, was used. All patients were assessed for clinical manifestations and underwent ECG, echocardiography, and HRCT at the study entry and then annually. Results: One hundred and fifteen patients (46 male, 90 dcSSc) with a mean (SD) disease duration of 11.6 months (8.8) at cohort entry were enrolled during a mean (SD) observational period of 3.8 years (1.6). At enrollment, the male group had a higher prevalence of dcSSc subtype (91.3% vs. 69.5%, p = 0.006), hypo-hyperpigmentation (84.8% vs. 65.2%, p = 0.021), myositis (26.1% vs. 10.1%, p = 0.024), and right ventricular dysfunction [RVD] (8.7% vs. 0%, p = 0.024) compared with women. At the last visit, the male group had a higher cumulative prevalence of digital ulcers (47.8% vs. 27.5%, p = 0.026), telangiectasia (93.5% vs. 69.6%, p = 0.002), joint contracture (69.6% vs. 43.5%, p = 0.006), tendon friction rub (39.1% vs. 20.3%, p = 0.027), LVEF < 50% (21.7% vs. 8.7%, p = 0.048), and RVD (34.8% vs. 7.2%, p < 0.001). The male group had a significantly higher incidence rate of RVD (8.21 vs. 1.99 per 100 person-years, p = 0.006) and interstitial lung disease [ILD] (65.25 vs. 40.36 per 100 person-years, p = 0.022) compared to women. Conclusions: In this study cohort, it was found that men with SSc had more severe clinical manifestations and higher incidence rate of RVD and ILD compared to women. Increased awareness of cardiopulmonary complications in men even in early phase of SSc is crucial. Key Points: • Male patients with SSc have more severe disease manifestations compared to women. • Even in the early phase of the disease, men were found to have higher incidence rates of right ventricular dysfunction and interstitial lung disease than women. • Increased awareness regarding cardiopulmonary complications in men with early SSc is crucial for effective management of these complications.